Культ святителя в сербській народній традиції - Питулич, В. (Народна творчість та етнологія, 2012)
Bearing in mind the polyvalence of oral storytelling, which is the result of its ancient origin and traces of the time it has passed through, the paper discusses the issue of the saint’s cult in Serbian folk tradition. In analyzing this problem, we started from the pre-Christian times in order to show what way the old, polytheistic religion was supplanted with the new, monotheistic and what role the saint’s cult plays in it.
In dealing with text in reported and direct speech, we have tried to point out only some moments essential to understanding this problem, which is the constant presence of the saints who, having been endowed by God with epiphany, have the function of maintaining harmony on earth.
The saint’s cult in folk tradition is highly developed, and we can find it in almost all forms of oral storytelling (lyric, epic, oral folk forms), which indicates the need for interdisciplinary study of their functions in different ethnopsychological communities. Имајући у виду поливаленцију усменог казивања, која представља резултат његовог древног порекла и трагова протеклих времена, рад разматра питање култа Светаца у српској фолклорној традицији. У анализи овог проблема, ми полазимо од прехришћанског времена да би показали начин на који је стара, политеистичка религија била замењена новом, монотеистичком, као и који је положај култа Светаца у њима.
Бавећи се индиректним и слободним говором, ми смо покушали да укажемо само на суштинске моменте у разумевању тог проблема сталне присутности Свеца који је обдарен Богом епифанијом, и има функцију одржавања хармоније на земљи.
Култ Светаца у народној традицији је веома развијен, и можемо га наћи у скоро свим формама усменог казивања (лирика, епика, усмене народне форме) што указује на потребу интердисциплинарног изучавања функција у различитим етнопсихолошким заједницама.